Síntese e caracterização de óxidos de ferro e compósitos para aplicações no tratamento redox de efluentes aquosos - Fabiano Magalhaes (2008)
In this work new materials based on iron oxides were prepared, characterized and used in environmental decontamination processes. The work is presented in five chapters. Chapter 1 presents a general introduction on Advanced Oxidation Process, iron oxides and objectives.In Chapter 2 chromium substituted magnetites (Fe3-xCrxO4 with x = 0,00; 0,07; 0,26; 0,42 e 0,51) were tested as catalysts for two reactions: (i) to decomposition of H2O2 to O2 and (ii) heterogeneous Fenton oxidations. The H2O2 decomposition rate increased as the Cr content in the magnetite increased. For the Fenton reaction with the model dyes methylene blue and drimaren red the best results were obtained for the low Cr content magnetite (Fe2.93Cr0.07O4).In Chapter 3 composites based on carbon and Fe3O4 and Feo prepared from tar and Fe2O3 were tested in three reactions: (i) Cr(VI) reduction to Cr(III), (ii) decomposition of H2O2 to O2 and (ii) oxidation of the dyes methylene blue with H2O2. The best results for Cr(VI) reduction were obtained for the composites treated at 800 0C whereas for the H2O2reactions the composite treated at 400-800oC showed the higher activities. In Chapter 4 hematite (-Fe2O3), goethite (FeOOH), maghemite (-Fe2O3) e magnetite (Fe3O4) were tested on the photocatalytic degradation of the dye drimaren red. Goethite showed the best results whereas -Fe2O3, -Fe2O3 e Fe3O4 showed a negative effect.In Chapter 5 composites based on iron oxides and TiO2: Fe2O3/TiO2, Fe3O4/TiO2, Fe0/Fe2O3/TiO2 and Fe0/TiO2 with different iron contents (1, 5, 10, 20 e 30 %) were tested for photocatalytic degradation of the dye drimaren red.